2021
DOI: 10.1590/0001-3765202120190557
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization of blue-and-yellow macaw (Ara ararauna) seasonal testicular variations in captivity

Abstract: The reproduction of monogamous wild birds in captivity it`s diffi cult and the apparent low fertility in males requires more investigations. The objective of the study was to test the hypothesis that wild bird species in captivity would present low reproductive potential, through the analysis of the morphological characteristics of Ara ararauna testicles, maintained in captivity, correlating them with the climate variations in the Cerrado Biome. For that, testicles were captured in April (dry) and October (rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Though few reports on histomorphological alterations of the testicular capsule during maturation of the testis are available (Aire & Ozegbe, 2007;Maretta & Marettová, 2004;Mohanty et al, 2017;Pandey & Mohanty, 2015); detailed information on the seasonal cyclicity of this distinct component of the testis is unavailable. This study demonstrated the seasonal histomorphological alterations in the testicular capsule in an estrildid bird, Amandava Moreira et al, 2021). It binds with AR and mediates paracrine regulation of intra-testicular functions to induce secondary sexual characters and spermatogenesis as well as the development of muscle mass.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Though few reports on histomorphological alterations of the testicular capsule during maturation of the testis are available (Aire & Ozegbe, 2007;Maretta & Marettová, 2004;Mohanty et al, 2017;Pandey & Mohanty, 2015); detailed information on the seasonal cyclicity of this distinct component of the testis is unavailable. This study demonstrated the seasonal histomorphological alterations in the testicular capsule in an estrildid bird, Amandava Moreira et al, 2021). It binds with AR and mediates paracrine regulation of intra-testicular functions to induce secondary sexual characters and spermatogenesis as well as the development of muscle mass.…”
Section: Discussionmentioning
confidence: 69%
“…The AR helps to facilitate intra‐testicular actions of testosterone by autocrine/paracrine signals through the testicular capsule during the breeding cycle. Testosterone plays a crucial role in the maintenance of reproductive homeostasis during the breeding phase (Carvalho et al, 2015; Moreira et al, 2021). It binds with AR and mediates paracrine regulation of intra‐testicular functions to induce secondary sexual characters and spermatogenesis as well as the development of muscle mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation